Analisis Intervensi Senam Diabetes dalam Upaya Menurunkan Kadar Gula Darah - Eni Hastuti (Journal of Telenursing (JOTING), 2020)
This study aims to determine the effect of diabetes exercise on reducing blood glucose levels in people with diabetes. This type of research is a quasi-experimental design non-equivalent control group design with a simple case study approach. A case study conducted in 5 days for 30 minutes showed that Diabetes Gymnastics was effective in reducing blood sugar levels in people with Diabetes Mellitus by 7.1%. In conclusion, diabetes exercises conducted for five consecutive days, effectively lower blood glucose levels in people with diabetes. Keywords: Diabetes Mellitus, Blood Sugar, Gymnastics